2016
DOI: 10.1016/j.chb.2016.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Investigating user switching intention for mobile instant messaging application: Taking WeChat as an example

Abstract: First, we appreciate the helpful comments and suggestions by the anonymous reviewers. We also would like to thank all the comments and suggestions when we presented the conceptual part of this study as a poster in PACIS 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 61 publications
1
45
1
4
Order By: Relevance
“…Therefore, it usually involves a partial replacement that the users use both services but rely more on the substitute. In line with previous studies (Peng, Zhao, & Zhu, 2016), we do not strictly define that a switching behavior should involve a complete abandon of incumbent service.…”
Section: Users' It Switching Behaviormentioning
confidence: 75%
See 3 more Smart Citations
“…Therefore, it usually involves a partial replacement that the users use both services but rely more on the substitute. In line with previous studies (Peng, Zhao, & Zhu, 2016), we do not strictly define that a switching behavior should involve a complete abandon of incumbent service.…”
Section: Users' It Switching Behaviormentioning
confidence: 75%
“…In both human migration (Curran & Saguy, 2013) and IT switching studies (Lai & Wang, 2015;Peng et al 2016;Zhou, 2016), trust shows significant impact on users' decision process. This construct has been divided into three types: institution-based trust, knowledge-based trust, and transfer trust.…”
Section: Pull Effect: Transfer Trustmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been highlighted by different scholars that there is a missing link between mobile advertising related factor and consumer related outcomes (Peng, Zhao, & Zhu, 2016;Venkatesh & Bala, 2008;Shin, 2015). Prominent researches (Lamberton & Stephen, 2016;Varnali & Toker, 2010) indicated that there is a need to study the mediated effect of mobile advertising related factor on consumer attitude through emotional value.…”
Section: Introductionmentioning
confidence: 99%